2023
DOI: 10.1021/jacs.2c12493
|View full text |Cite
|
Sign up to set email alerts
|

Two Color Imaging of Different Hypoxia Levels in Cancer Cells

Abstract: Hypoxia (low oxygen levels) occurs in a range of biological contexts, including plants, bacterial biofilms, and solid tumors; it elicits responses from these biological systems that impact their survival. For example, conditions of low oxygen make treating tumors more difficult and have a negative impact on patient prognosis. Therefore, chemical probes that enable the study of biological hypoxia are valuable tools to increase the understanding of disease-related conditions that involve low oxygen levels, ultim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 54 publications
1
20
0
Order By: Relevance
“…We have previously shown that compounds which are bioreduced in this assay also undergo bioreduction in a cellular setting. 15,17,[25][26][27][28][29] Treatment with CYPreductase (CYP004, expressed in Escherichia coli, purchased from Cypex ® ) in hypoxia resulted in bioreduction of EF5-DCM (4) to yield DCM (5) as judged by HPLC analysis and fluorescent spectroscopy (Figure S1). A fluorescence recovery of 61% was observed after 30 h, and a peak consistent with this level of DCM release was detected using HPLC analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that compounds which are bioreduced in this assay also undergo bioreduction in a cellular setting. 15,17,[25][26][27][28][29] Treatment with CYPreductase (CYP004, expressed in Escherichia coli, purchased from Cypex ® ) in hypoxia resulted in bioreduction of EF5-DCM (4) to yield DCM (5) as judged by HPLC analysis and fluorescent spectroscopy (Figure S1). A fluorescence recovery of 61% was observed after 30 h, and a peak consistent with this level of DCM release was detected using HPLC analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The scientific rationale for using a HAP to treat patients with multiple myeloma is supported by the fact that both evofosfamide and tirapazamine have been tested clinically in this context. 25,33 The lack of success with these agents can be partially attributed to the lack of patient stratification for hypoxia. By building in the ability to image prodrug delivery and activation, as shown here with EF5-Pano, it becomes possible to fully characterize the mechanism of action of EF5-Pano (2), and HAPs more widely, preclinically.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that compounds which are bioreduced in this assay also undergo bioreduction in a cellular setting. 12,[15][16][17][23][24][25] Treatment with CYP-reductase (CYP004, expressed in Escherichia coli, purchased from Cypex ® ) in hypoxia resulted in bioreduction of EF5-DCM (4) to yield DCM (5) as judged by fluorescent spectroscopy (Figure S1) and HPLC analysis (Figure S2). A fluorescence recovery of 61% was observed after 30 h, and a peak consistent with this level of DCM release was detected using HPLC analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The scientific rationale for using a HAP to treat patients with multiple myeloma is supported by the fact that both evofosfamide and tirapazamine have been tested clinically in this context. 23,28 The lack of success with these agents can be partially attributed to the lack of patient stratification for hypoxia. By building in the ability to image prodrug delivery and activation, as shown here with EF5-Pano, it becomes possible to fully characterize the mechanism of action of EF5-Pano (2), and HAPs more widely, preclinically.…”
Section: Discussionmentioning
confidence: 99%
“…Regions of hypoxia occur in most solid tumors as a result of inefficient vasculature and the high metabolic demand of cancer cells . Due to its correlation to chemo- and radiotherapy resistance, , extensive efforts have been devoted to exploiting the bioreductive nature of tumor hypoxia to catalyze a wide range of biotransformations for diagnostic and therapeutic purposes. However, few studies have focused on the hypoxia-mediated bioreduction of Pt­(IV) to Pt­(II) nor its direct visualization to understand the differences between reduction and toxicity. We therefore set out to test OxaliRes and OxaliNap in hypoxic conditions. To start, HCT116 cells were exposed to severe levels of hypoxia (<0.1% O 2 ) in the presence of OxaliRes or OxaliNap.…”
mentioning
confidence: 99%